Formulasi Perjanjian Baku Dalam Rangka Perlindungan Hukum Konsumen PT. PLN - Indra Muchlis Adnan; Sukamto Satoto; Dwi Suryahartati (Universitas Pendidikan Nasional, 2022)
This study examines the legal consequences in the standard agreement between State Electricity Company (PT. PLN) as a public interest service provider company with consumers. This research study focuses on; First, legal protection for consumers if PT. PLN as a public interest service provider company does not fulfill its obligations in the power purchase agreement. Second, dispute resolution between consumers and PT. PLN. The purpose of this research is to contribute to the development of legal science in the field of Consumer Protection Law. The theoretical and practical benefits of this research are expected to contribute to the development of notarial law, especially regarding the formulation of standard agreements in the context of consumer legal protection of PT. PLN. This type of research is normative, or also known as library research. The study concludes that the legal protection of electricity customers in relation to the power purchase agreement letter (SPJBTL) has not been fully implemented. Regarding dispute resolution, it is possible for consumers to resolve through non-litigation legal channels, namely through the Consumer Dispute Resolution Agency (BPSK), because BPSK is easier, cheaper, faster, and simpler, in this case BPSK acts as a mediator in resolving electricity consumer disputes.